Ανάπτυξη συστήματος ταυτοποίησης προσώπων και αντικειμένων με χρήση μικροεπεξεργαστών ανοικτού λογισμικού και τεχνολογίας RFID - Πλέσσας, Παναγιώτης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Τεχνολογίας Πληροφορικής και Υπολογιστών. Εργαστήριο Μικροϋπολογιστών και Ψηφιακών Συστημάτων VLSI, 2015)
The Radio frequency identification systems (RFID) have attracted an enormous interest during the recent years and they are expected to become soon the prevailing technology in the automatic identification and data capture systems. This interest comes from both the academic research community and the rest potential technology stakeholders. This dissertation has two aims. Firstly, to give a general introduction into the basic structure, the theory of operation and the applications of the RFID systems and secondly, to present in detail the design of a particular access control system. Chapter 1 makes a throwback in both the creation of Arduino Project but also to the fundamental principles of RFID systems, along with their history as a technological branch of radar systems and as a complementary technology to the currently prevailing barcode technology. In addition, chapter 2 presents analytical components and detail examination for the technical characteristics of RFID system.